2008
DOI: 10.1086/528806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus Infection onStreptococcus pneumoniaeColonization and Seroepidemiology among Zambian Women

Abstract: Nasopharyngeal colonization with Streptococcus pneumoniae precedes invasive pneumococcal disease. Human immunodeficiency virus (HIV) infection increases rates of invasive pneumococcal disease, and its effect on colonization is unknown. In a longitudinal cohort of Zambian mothers with or without HIV infection, HIV infection increased the risk of colonization (risk ratio [RR], 1.9; 95% confidence interval [CI], 1.3-2.8) and repeat colonization (RR, 2.4; 95% CI, 1.1-5.3) and reduced the time to new colonization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…HIV-infected African adults have increased risk of repeat colonization [18], persistently poor control of pneumococcal colonization and as a result high rates of colonization compared to non-infected adults [8]. We propose that increased IgG responses observed in BAL in the HIV-infected group are a consequence of their higher rates of carriage and previous infection.…”
Section: Discussionmentioning
confidence: 85%
“…HIV-infected African adults have increased risk of repeat colonization [18], persistently poor control of pneumococcal colonization and as a result high rates of colonization compared to non-infected adults [8]. We propose that increased IgG responses observed in BAL in the HIV-infected group are a consequence of their higher rates of carriage and previous infection.…”
Section: Discussionmentioning
confidence: 85%
“…Gill et al reported that HIV-infected African women were 1.9 fold more likely to be colonized by pneumococcus - especially serogroups 6, 19 and 23- than HIV-uninfected women. (16)…”
Section: Discussionmentioning
confidence: 99%
“…In their study, sputum lytA qPCR had the best sensitivity and specificity with a cutoff value of 10 5 DNA copies/ml (10). The prevalence and density of pneumococcal nasopharyngeal colonization vary with age, with HIV serostatus, and in different geographic areas (11)(12)(13). It is unknown whether pneumococcal loads in sputum vary in different populations, as they have only been reported for adults in high-income countries.…”
mentioning
confidence: 96%